Institutional repository as an information infrastructure for scholarly communication: An exploratory study in Indonesia - Nurdin, L.; Mukhlis, S. (Malaysian Journal of Library and Information Science, 2019)
The objective of this study was to understand the proper implementation of the institutional repositories (IRs) as an infrastructure for scholarly communication. The study employed a descriptive-qualitative approach to explore how the IRs are operated in three selected universities in Indonesia. Three types of data collection techniques were used: interviews, observation, and document analysis. Structured interview was used as the main data collection technique. Findings of the study are presented in four main aspects in the implementation of IRs, i.e. development of scientific works; processing or recruitment of scientific works through self-archiving and digitization; promotion of IRs in increasing its visibility; and distribution or dissemination of the local scientific works by libraries. Although all three universities have adopted an open access policy which requires their academic community to make their scholarly works available in the freely accessible IRs, the distribution model differs in terms of the degree of openness. It seems that the value of a repository and open access ideals are quite enough to significantly increase faculty and students participation to populate the IRs. This study is significantly useful for readers, especially in the context of a developing country, to know the crucial position of the IRs as an infrastructure that frames the scholarly communication at universities.